Shikimate Kinase 1 from Klebsiella pneumoniae as a New Drug Target Enzyme: Insights from Comparative Modeling and Molecular Dynamics - Yanping Li
Klebsiella pneumoniae, a Gram-negative bacterium, is an established nosocomial pathogen that is particularly dangerous to immunosuppressed individuals, causing diseases such as sepsis, pneumonia, urinary tract infections and respiratory tract infections. The emergence of multidrug resistant strains of this bacterium poses a significant challenge to current therapeutic strategies, highlighting the urgent need for new drug targets.